Determinan Carbon Emission Disclosure pada Perusahaan Sektor Consumer Non-Cyclical Tahun 2020-2023 - Mohammad Mirza Rafiudin; Munari Munari (Owner : Riset dan Jurnal Akuntansi, 2025)
The industrial sector, particularly the non-cyclical consumer sector, is a significant contributor to greenhouse gas emissions. As a result, it is expected to take an active role in efforts to combat climate change. This study aims to analyze the influence of environmental performance, earnings growth, firm size, and profitability on carbon emissions disclosure (CED). The research focused on 125 non-cyclical consumer companies listed on the Indonesia Stock Exchange (IDX) between 2020 and 2023. Using purposive sampling, 35 companies were selected as the sample, yielding 140 observation units. This quantitative study utilized secondary data obtained from company annual reports and sustainability reports. Panel data regression analysis was applied, with the random effects model identified as the most suitable. The F-test results indicate that the regression model is appropriate and can collectively explain variations in CED. Meanwhile, partial test results reveal that earnings growth has no significant impact on CED, while profitability, firm size, and environmental performance do have a significant effect.